2017
DOI: 10.1016/j.jsbmb.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Differences in testosterone and its precursors by sex of the offspring in meconium

Abstract: Prenatal metabolism exerts profound effects on development. The first stool of the newborn, meconium, provides a window into the prenatal metabolic environment. The objective of this study was to examine the feasibility of meconium as a novel matrix to quantify prenatal steroid levels. We quantified parameters of analytical interest regarding the use of meconium, including sample stability. We hypothesized that meconium steroid content would differ by sex, prompting analysis of meconium to test effects of pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…This has been used to quantify maternal use of drugs of abuse and environmental exposures during pregnancy 14 , anti-retroviral pharmacokinetics 18 , metabolomics during gestational diabetes 19 , and fetal sex steroid metabolism 20 . To our knowledge, this is the first meconium report of the transplacental pharmacokinetics of chemotherapeutics in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been used to quantify maternal use of drugs of abuse and environmental exposures during pregnancy 14 , anti-retroviral pharmacokinetics 18 , metabolomics during gestational diabetes 19 , and fetal sex steroid metabolism 20 . To our knowledge, this is the first meconium report of the transplacental pharmacokinetics of chemotherapeutics in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Since starting the current project, 30 women have enrolled and received chemotherapy, and 23 have agreed to collect meconium at the time of delivering their child. The majority of women in the study (20) were treated for breast cancer, 1 for colon cancer and 2 for Hodgkin's Lymphoma. As the study is ongoing, full un-blinding of treatment regimens is not possible.…”
Section: Study Populationmentioning
confidence: 99%
“…Other studies using either amniotic fluid or cord blood reported mixed, but mostly null results. (24)(25)(26)(27) To overcome the limitations of amniocentesis and cord blood, we used meconium, the first stool of a newborn, to estimate prenatal androgen exposure. Since formation of meconium is thought to start around the 12-13 th week of gestation, and meconium can be non-invasively collected within 72 hours of the birth of the child, meconium has the potential to capture cumulative prenatal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Since formation of meconium is thought to start around the 12-13 th week of gestation, and meconium can be non-invasively collected within 72 hours of the birth of the child, meconium has the potential to capture cumulative prenatal exposure. (28). Previous studies have utilized meconium samples to examine prenatal exposure to both exogenous and endogenous compounds, (29)(30)(31) and we recently developed a robust method to quantify androgens in human meconium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation